Accountable artefacts: the case of the Carolan guitar - Benford, Steve; Hazzard, Adrian; Chamberlain, Alan; Glover, Kevin; Greenhalgh, Chris; Xu, Liming; Hoare, Michaela; Darzentas, Dimitrios (2016)
We explore how physical artefacts can be connected to digital records of where they have been, who they have encountered and what has happened to them, and how this can enhance their meaning and utility. We describe how a travelling technology probe in the form of an augmented acoustic guitar engaged users in a design conversation as it visited homes, studios, gigs, workshops and lessons, and how this revealed the diversity and utility of its digital record. We describe how this record was captured and flexibly mapped to the physical guitar and proxy artefacts. We contribute a conceptual framework for accountable artefacts that articulates how multiple and complex mappings between physical artefacts and their digital records may be created, appropriated, shared and interrogated to deliver accounts of provenance and use as well as methodological reflections on technology probes.